2009
DOI: 10.1002/app.30161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different interphases on the mechanical properties of cured silanized silica‐filled styrene–butadiene/polybutadiene rubber blends for use in passenger car tire treads

Abstract: Polybutadiene (BR) and styrene-butadiene (SBR) rubbers containing the same loading of precipitated silica nanofiller were prepared. The silica surfaces were pretreated with bis(3-triethoxysilylpropyl) tetrasulfide to chemically bond the silica to the rubber. The rubber compounds were mixed together for different times and at different temperatures to produce SBR/BR blends. The mass fraction and composition values of the interphases in the blends were subsequently determined with modulated-temperature different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…C1 and N1 exhibited lower compression heat buildups (10–15°C) and compression permanent sets (2–3%) than those (18–48°C and 10–35%) reported by Peng et al A similar superiority was also reflected in a comparison with Kar's report . The compression permanent set of 5.8–6.2% and the compression heat buildups of 62.5–67°C and even 40.8–54.2°C and 85.7–92.3°C were higher than those in our study; this showed the advantage of cocoagulation technique.…”
Section: Resultssupporting
confidence: 61%
“…C1 and N1 exhibited lower compression heat buildups (10–15°C) and compression permanent sets (2–3%) than those (18–48°C and 10–35%) reported by Peng et al A similar superiority was also reflected in a comparison with Kar's report . The compression permanent set of 5.8–6.2% and the compression heat buildups of 62.5–67°C and even 40.8–54.2°C and 85.7–92.3°C were higher than those in our study; this showed the advantage of cocoagulation technique.…”
Section: Resultssupporting
confidence: 61%
“…In addition, when the SBR and BR rubbers were mixed together for 12 min to produce compounds 46 and 47 and then cured at 170 o C for up to 13 min, a strong interphase was formed between the two rubbers. 44,45 The development of a strong interphase between dissimilar rubbers is an important factor in the durability and performance of rubber blends in service.…”
Section: Mechanical Properties Of the Cured Sbr/br Rubber Blendsmentioning
confidence: 99%
“…The silica and silane-based styrene-butadiene rubber/ polybutadiene rubber (SBR/BR) composites are currently being used in passenger car radial tire-tread [21]. In the present study, the commercial-grade high cis-polybutadiene rubber (BR) was epoxidized to synthesize epoxy-BR (EBR) at different epoxidation magnitude, and thus, prepared EBRs were used to replace and/or reduce the coupling agent from SBR/BR composites.…”
Section: Introductionmentioning
confidence: 99%